Review of the monograph "Molev E.A., Moleva N.V. Bosporan city of Kitey: monograph. Part III. – Nizhny Novgorod: Nizhny Novgorod state university publishing house, 2022. – 453 p.: with ill., table." - Yuzanna M. Azikova; Khamitbi B. Mamsirov (Кавказология, 2023)
The review analyzes the monograph by Evgeny Alexandrovich Molev and Natalia Vladimirovna Moleva "The Bosporan city of Kitei: Monograph. Part III", dedicated to the results of excavations in the field seasons 2005-2012 and 2016-2017. The preparation and publication of the fundamental work were the result of many years of research into the ancient city of Kitei. At the time of publication of the monograph, one of the authors of the work, Yevgeny Alexandrovich Molev, passed away. But the debt of memory and respect for the famous Russian archaeologist and antiquarian prompted his colleagues and associates, led by Alexander Valentinovich Makhlayuk, to complete the work and publish it.Evgeny Alexandrovich was a great friend of Kabardino-Balkarian State University named after H.M. Berbekov. After the collapse of the USSR, the eminent Russian scientist made every effort to restore comprehensive ties between Lobachevsky Nizhny Novgorod State University and Kabardino-Balkarian State University named after H.M. Berbekov. This was reflected in the participation of colleagues in international and all-Russian conferences, the opposition of candidate and doctoral dissertations, in performances as a leading organization, the preparation of reviews of dissertations, monographs and textbooks.For 15 years he was the chairman of the State Attestation Commission in the field of History. His high competence and professionalism made it possible to objectively assess the quality of the training of graduate historians, to be on top of the requirements for modern specialists. Evgeny Alexandrovich published his articles in the electronic journal "Kavkazologiya" when he took his first steps.Therefore, we could not remain indifferent to the appearance of the latest monograph by E.A. Molev. The topic studied in the monograph is certainly relevant. For kavkazologists, it is interesting because it provides a new layer of knowledge about the interaction in the ancient era of the Greek cities of Bosporus and the Sinds and Meots, which is fully correlated with the identical studies of R.J. Betrozov in the Northwestern Caucasus.The structure of the work is clear and well-founded. The scientific content of the sections is relevant to existing academic standards. The publication deserves the highest appreciation and attention of the historical and archaeological community.